Drought-resistant trait of different crop genotypes determines assembly patterns of soil and phyllosphere microbial communities - Baobei Guo; Hong Zhang; Yong Liu; Jianwen Chen; Junjian Li (Microbiology Spectrum, 2023)
ABSTRACT Crop microbiomes are widely recognized to play a role in crop stress resistance, but the ecological processes that shape crop microbiomes under water stress are unclear. Therefore, we investigated the bacterial communities of two oat (Avena sativa) and two wheat (Triticum aestivum) genotypes under different water stress conditions. Our results show that the microbial assemblage was determined by the crop compartment niche. Host selection pressure on the bacterial community increased progressively from soil to epiphyte to endophyte pathways, leading to a decrease in bacterial community diversity and network complexity. Source tracing shows that soil is the primary source of crop microbial communities and that bulk soil is the main potential source of crop microbiota. It filters gradually through the different compartment niches of the crop. We found that the phyla Actinobacteria, Proteobacteria, Gemmatimonadota, and Myxococcota were significantly enriched in bacterial communities associated with crop-resistance enzyme activity. Crop genotype influenced the composition of the rhizosphere soil microbial community, and the composition of the phylloplane microbial community was affected by water stress. IMPORTANCE In this paper, we investigated the assembly of the plant microbiome in response to water stress. We found that the determinant of microbiome assembly under water stress was the host type and that microbial communities were progressively filtered and enriched as they moved from soil to epiphyte to endophyte communities, with the main potential source being bulk soil. We also screened for bacterial communities that were significantly associated with crop enzyme activity. Our research provides insights into the manipulation of microbes in response to crop resistance to water stress.